Intravenous immunoglobulin as an adjunct therapy in persisting heparin-induced thrombocytopenia. Issue 4 (August 2018) - Park, B.D.; Kumar, M.; Nagalla, S.; De Simone, N.; Aster, R.H.; Padmanabhan, A.; Sarode, R.; Rambally, S.
Abstract: Heparin induced thrombocytopenia (HIT) is a serious adverse drug reaction caused by transient antibodies against platelet factor 4 (PF4)/heparin complexes, resulting in platelet activation and potentially fatal arterial and/or venous thrombosis. Most cases of HIT respond to cessation of heparin and administration of an alternative non-heparin anticoagulant, but there are cases of persisting HIT, defined as thrombocytopenia due to platelet activation/consumption for greater than seven days despite standard therapy. These patients remain at high risk for thrombotic events, which may result in limb-loss and mortality. Intravenous immunoglobulin (IVIg) has been proposed as an adjunct therapy for these refractory cases based on its ability to saturate FcγRIIa receptors on platelets, thus preventing HIT antibody binding and platelet activation. We describe 2 cases of persisting HIT (strongly positive antigen and functional assays, and persisting thrombocytopenia >7 days) with rapid clinical response to IVIg. We performed in-vitro experiments to support IVIg response. Healthy donor platelets (1 × 10e6) were treated with PF4 (3.75 μg/mL) for 20 min followed by 1-hour incubation with patients' sera. Platelet activation with and without addition of IVIg (levels equivalent to those reached in a patient after treatment with 2 gm/Kg) was evaluated in the PF4-dependent P-selectin expression assay (PEA). A significantly decreased platelet activation was demonstrated after the addition of IVIg to both patient samples, which correlated well with the rapid clinical response that each patient experienced. Thus, our study supports the use of IVIg as an adjunct therapy for persisting HIT.